OXIDATIVE AND ANTIOXIDANT STATUS IN DEPRESSIVE DISORDER PATHOLOGY - Sanggary Marimuthu (E-Jurnal Medika Udayana, 2013)
Depressive disorder is a psychiatric disorder often found lately. Oxidative stress is a mechanism that promotes the occurrence of major depressive disorder. Oxidative stress is defined as an imbalance between oxidants and antioxidants whereby high oxidant content is due to decrease the antioxidant cap city of the system. Objective: The aim of this study is to assess the oxidative and antioxidative status in plasma in patients diagnosed with clinical depression, and to assess whether there is a relationship between oxidative stress and severity of depression. Methods: In this study we gather 50 patients with depression according to the Diagnostic and Statistical Manual of Mental Disorders fourth edition and 20 healthy control subjects. Activity levels of plasma malondialdehyde, superoxide dismutase and glutathione peroxidase were measured in this study to assess the oxidative status and antioxidative defense prior to antidepressant medication. Results: Patients with depression had higher total plasma peroxide and lower plasma antioxidants than controls. Depressed oxidative stress index values patients were significantly higher than controls, and there is a significant positive correlation between the scale and the Hamilton depression Rating Oxidative stress index value. Conclusion: Patients with major depression are exposed to oxidative stress, and oxidative stress index may be useful to reflect the severity of the disease.